A Prospective Study on Child Abuse and Elder Mistreatment: Assessing Direct Effects and Associations With Depression and Substance Use Problems During Adolescence and Middle Adulthood. Issue 3 (20th August 2021) - Herrenkohl, Todd I; Roberto, Karen A; Fedina, Lisa; Hong, Sunghyun; Love, Jasmine
Abstract: Background and Objectives: We examined the prospective association between 2 measures of child abuse, one based on official child welfare records and the other based on parent self-reports, and the perpetration of elder mistreatment by an adult child. We also examined measures of adolescent and adult depression and substance use problems as predictors of elder mistreatment. Research Design and Methods: Data are from a prospective study that began in the 1970s with a sample of children aged 18 months to 6 years of age. Analyses draw on data collected when child participants were in preschool and elementary school, when they were adolescents, and as adults at midlife (at ages 36 and 46, on average). Results are from bivariate correlations and multivariable path models in which variables from different life stages were entered in steps to assess their prediction of elder mistreatment. Results: All variables were significantly correlated with elder mistreatment. In a final path model, parent self-reports of physical child abuse remained a significant, unique predictor of elder mistreatment. Adolescent and adult substance use problems were also statistically significant. Discussion and Implications: Few longitudinal studies have tracked patterns of abuse over time and relationships. Findings suggest that child abuse is a risk factor for the perpetration of elder mistreatment by an adult child. Substance use problems may also increase the risk for the perpetration of elder mistreatment. Further longitudinal research is needed to replicate and extend these findings in order to advance prevention and intervention programs and policies.